The Effects of Menstrual Cycle Phases and Adiposity on Energy Balance in Women - McNeil, Jessica N. (Université d'Ottawa / University of Ottawa, 2011)
Energy intake (EI) and energy expenditure (EE) across the menstrual cycle (MC), while considering body adiposity, have not been previously evaluated in the same individuals. This study mainly examined the variations in energy balance (EB) across MC. Seventeen women (Body fat-DXA:28.5%) participated in three identical sessions during distinct phases of the MC: Early-follicular, Late-follicular/ovulation and Mid-luteal (confirmed by basal temperature and sex-steroid hormones). EI, resting metabolic rate (RMR), physical-activity EE (PAEE), severity of PMS, leptin and relative-reinforcing value (RRV) of preferred foods were measured during each phase. No differences in body fat, EI, RMR, PAEE, leptin and RRV of food were noted across MC. Trends were noted in preferred snack (p=0.06) and combined snack/fruit (p=0.06) intakes, while differences were noted in severity of PMS (p<0.05) across phases. Changes in EB across the MC were not noted. PMS was more severe, and preferred snack and combined snack/fruit intakes were slightly higher during mid-luteal phase.
Keywords: menstrual cycle; energy intake; resting metabolic rate; physical activity energy expenditure; premenstrual syndrome; relative reinforcing value of food; leptin